Case file coding of child maltreatment: Methods, challenges, and innovations in a longitudinal project of youth in foster care. (August 2016) - Huffhines, Lindsay; Tunno, Angela M.; Cho, Bridget; Hambrick, Erin P.; Campos, Ilse; Lichty, Brittany; Jackson, Yo
Abstract: State social service agency case files are a common mechanism for obtaining information about a child's maltreatment history, yet these documents are often challenging for researchers to access, and then to process in a manner consistent with the requirements of social science research designs. Specifically, accessing and navigating case files is an extensive undertaking, and a task that many researchers have had to maneuver with little guidance. Even after the files are in hand and the research questions and relevant variables have been clarified, case file information about a child's maltreatment exposure can be idiosyncratic, vague, inconsistent, and incomplete, making coding such information into useful variables for statistical analyses difficult. The Modified Maltreatment Classification System (MMCS) is a popular tool used to guide the process, and though comprehensive, this coding system cannot cover all idiosyncrasies found in case files. It is not clear from the literature how researchers implement this system while accounting for issues outside of the purview of the MMCS or that arise during MMCS use. Finally, a large yet reliable file coding team is essential to the process, however, the literature lacks training guidelines and methods for establishing reliability between coders. In an effort to move the field toward a common approach, the purpose of the present discussion is to detail the process used by one large-scale study of child maltreatment, the Studying Pathways to Adjustment and Resilience in Kids (SPARK) project, a longitudinal study of resilience in youth in foster care. The article addresses each phase of case file coding, from accessing case files, to identifying how to measure constructs of interest, to dealing with exceptions to the coding system, to coding variables reliably, to training large teams of coders and monitoring for fidelity. Implications for a comprehensive and efficient approach to case file coding are discussed. Highlights: The process of coding case files for child maltreatment history is rarely illustrated. A longitudinal project of youth in foster care shares important lessons learned about case file coding. Building relationships, developing new rules to categorize case file information, and training coders is vital.